2015
DOI: 10.1007/s00604-015-1539-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grain-size on the ethanol vapor sensing properties of room-temperature sputtered ZnO thin films

Abstract: We have investigated the gas sensing properties of ZnO thin films (100 to 200 nm thickness) deposited by roomtemperature radio frequency magnetron sputtering. The sensitivity of the films to ethanol vapor was measured in the 10 to 50 ppm concentration range at operating temperatures between 200 and 400°C. A synergetic effect of decreasing grain size and increasing operating temperature was observed towards the improvement of the sensitivity, reaching a value of 54 and a limit of detection as low as 0.61 ppm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…In this work, the TiO 2 /Pt/TiO 2 sandwich nanostructures were prepared by sputtering technique and were used as sensing material for ethanol, methanol, and 2-propanol detection in the sensor response results of the TiO 2 /Pt/TiO 2 sandwich nanostructures to the recent researches on ethanol sensing which are mostly based on ZnO, SnO 2 , and TiO 2 with various structures, such as nanoparticle, nanosphere, core-shell, nanotube and thin film, and various doping conditions [12][13][14][15][16][17][18]; it was found that the TiO 2 /Pt/TiO 2 sandwich nanostructures show advantages in terms of 10 ppm level sensitivity, roomtemperature operation, and stability. However, Ag@TiO 2 core-shell nanoparticles show the highest sensitivity down to 0.15 ppm ethanol with a fast response time and a fast recovery time but its fabrication process relies on wet process, which is time-consuming [15].…”
Section: Sensing Performance Of Gas Sensors Of Ethanol Methanol Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the TiO 2 /Pt/TiO 2 sandwich nanostructures were prepared by sputtering technique and were used as sensing material for ethanol, methanol, and 2-propanol detection in the sensor response results of the TiO 2 /Pt/TiO 2 sandwich nanostructures to the recent researches on ethanol sensing which are mostly based on ZnO, SnO 2 , and TiO 2 with various structures, such as nanoparticle, nanosphere, core-shell, nanotube and thin film, and various doping conditions [12][13][14][15][16][17][18]; it was found that the TiO 2 /Pt/TiO 2 sandwich nanostructures show advantages in terms of 10 ppm level sensitivity, roomtemperature operation, and stability. However, Ag@TiO 2 core-shell nanoparticles show the highest sensitivity down to 0.15 ppm ethanol with a fast response time and a fast recovery time but its fabrication process relies on wet process, which is time-consuming [15].…”
Section: Sensing Performance Of Gas Sensors Of Ethanol Methanol Andmentioning
confidence: 99%
“…The nanostructured materials, such as nanoparticle, nanowire, nanorod, and nanotube have demonstrated excellent sensing performance compared to conventional thin films [8][9][10][11][12][13][14][15][16][17][18][19][20]. The high selectivity of the sensors has been improved by surface modification with noble metals such as Pt and Pd [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Among various types of gas sensors, the resistive-type are common because of their stability, excellent performances, low cost, and simplicity of their operation [4][5][6][7]. It is known that size, surface structure and morphology of the sensing materials greatly influence their performances; hence, many efforts have been applied to synthesize gas sensors with various morphologies and surface structures [8][9][10][11][12]. One-dimensional (1D) nanowires can exhibit excellent gas sensing performance due to providing high surface area [13].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the conductivity declines sharply since the conduction channels between the grains will vanish. In the case of D ≥ 2L D , the depletion region around each neck forms a constricted conduction channel within each aggregate [25,26].…”
Section: Introductionmentioning
confidence: 99%